Cytokine‐Induced and Stretch‐Induced Sphingosine 1‐Phosphate Production by Enthesis Cells Could Favor Abnormal Ossification in Spondyloarthritis. (10th September 2019) - El Jamal, Alaeddine; Briolay, Anne; Mebarek, Saida; Le Goff, Benoit; Blanchard, Frédéric; Magne, David; Brizuela, Leyre; Bougault, Carole
ABSTRACT: Spondyloarthritis (SpA) is a common rheumatic disease characterized by enthesis inflammation (enthesitis) and ectopic ossification (enthesophytes). The current pathogenesis model suggests that inflammation and mechanical stress are both strongly involved in SpA pathophysiology. We have previously observed that the levels of sphingosine 1‐phosphate (S1P), a bone anabolic molecule, were particularly high in SpA patients' serum compared to healthy donors. Therefore, we wondered how this deregulation was related to SpA molecular mechanisms. Mouse primary osteoblasts, chondrocytes, and tenocytes were used as cell culture models. The sphingosine kinase 1 ( Sphk1 ) gene expression and S1P secretion were significantly enhanced by cyclic stretch in osteoblasts and chondrocytes. Further, TNF‐α and IL‐17, cytokines implicated in enthesitis, increased Sphk1 mRNA in chondrocytes in an additive manner when combined to stretch. The immunochemistry on mouse ankles showed that sphingosine kinase 1 (SK1) was localized in some chondrocytes; the addition of a pro‐inflammatory cocktail augmented Sphk1 expression in cultured ankles. Subsequently, fingolimod was used to block S1P metabolism in cell cultures. It inhibited S1P receptors (S1PRs) signaling and SK1 and SK2 activity in both osteoblasts and chondrocytes. Fingolimod also reduced S1PR‐induced activation by SpA patients' synovial fluid (SF), demonstrating that the stimulation of chondrocytes by SFs from SpA patients involves S1P. In addition, when the osteogenic culture medium was supplemented with fingolimod, alkaline phosphatase activity, matrix mineralization, and bone formation markers were significantly reduced in osteoblasts and hypertrophic chondrocytes. Osteogenic differentiation was accompanied by an increase in S1pr s mRNA, especially S1P1/3, but their contribution to S1P‐impact on mineralization seemed limited. Our results suggest that S1P might be overproduced in SpA enthesis in response to cytokines and mechanical stress, most likely by chondrocytes. Moreover, S1P could locally favor the abnormal ossification of the enthesis; therefore, blocking the S1P metabolic pathway could be a potential therapeutic approach for the treatment of SpA. © 2019 American Society for Bone and Mineral Research.